Factors that influence fatigue status in patients with severe rheumatoid arthritis (RA) and good disease outcome following 6 months of TNF inhibitor therapy: a comparative analysis - Mc Kee, Gabrielle (My University, 2015)
The objective of the present study is to determine the factors associated with persistent fatigue in patients with severe rheumatoid arthritis (RA) and good disease response to 6 months of tumour necrosis factor inhibitor therapy. Eligible patients with either persistent (PF) or no fatigue (NF) were compared. Using validated questionnaires and bivariate analysis, this cross-sectional survey explored if clinical characteristics, pain, self-efficacy, sleep and mood/depression differed between groups. Patients with PF (PF; NF) (n = 28; 28) reported significantly more overall pain (11.3 ± 9.4 (0-33); 6.9 ± 8.9 (0-33)), more recent and current pain intensity (41.4 ± 26.6 (0-80) 24.4 ± 26.6 (0-100) and depression (11.8 ± 7.5 (1-35); 8.2 ± 6.6 (0-26)), than the NF group. There was no significant difference between groups in self-efficacy and both groups experienced poor sleep quality (Pittsburgh Sleep Quality Index >5). Despite having good disease response, the PF group had significantly higher rheumatoid factor incidence, disease activity score-28, early morning stiffness duration and lower incidence of ever-failing disease-modifying anti-rheumatic drugs than the NF group. These findings enhance the fatigue literature in patients with RA prescribed tumour necrosis factor (TNF) inhibition therapy, identifying the potentially modifiable factors of pain and depression, previously demonstrated to be strongly associated with fatigue in non-biologic populations. In addition, this study highlights the association between persistent fatigue and an on-going state of low disease activity. This infers that more judicious disease management could minimise the symptom burden of pain and depression and consequentially fatigue.
PUBLISHED
Keywords: Disease outcome; Fatigue; Pain; Rheumatoid arthritis; Self-efficacy